Behaviour on health issues amidst COVID-19 lockdown- a study from Kolkata and neighbouring areas - Sen, Dr. Bandana; Mukherjee (Kundu), Dr. Shampa (Jour Med Resh and Health Sci, 2021)
This paper examines the implications of the COVID-19 pandemic for health related issues. It outlines contemporary evidence of inequalities in pandemics through information collected through a survey taken up during last fortnight of May 2020 from 2088 households at Kolkata and its neighbouring districts of West Bengal, India. It then examines whether there exists any inequality resulted by the lock-down to prevent COVID-19 pandemic among these households which are of different socio-economic strata. It then explores the potential consequences if any, of the lockdown measures implemented abruptly in India as a response to the COVID-19 pandemic. The essay concludes by mentioning the marginal analysis with different R0.